Investigating the mediating role of anxiety in academic burnout and academic performance of rehabilitation sciences students - Mohammad Hasan Keshavarzi; Seyed Hassan Saneii; Seyedeh Zahra Nahardani; Hamid Reza Koohestani; Noushin Kohan; Mahmoud Mansouri (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Mental disorders during student life can have destructive effects on students' learning and academic progress. This study was conducted to investigate the mediating role of anxiety variable in academic burnout and academic performance in students studying Rehabilitation at the Iran University of Medical Sciences (IUMS). MATERIALS AND METHODS: The current research enjoys a descriptive and correlational design. The statistical population consisted of all rehabilitation students of IUMS in 2022. The total number of students was 475; finally, 213 were randomly recruited as samples. The sample size was obtained using Cochran's formula. Using Pearson's correlation coefficient, simple relationships of variables were used. The data was analyzed by SPSS software version 25, using the path analysis. The path analysis was used to investigate the mediating role of anxiety. RESULTS: There is a significant negative correlation between academic burnout and academic performance (P < 0.002; r = −0.223). Also, there is a negative and significant correlation between the mediator variable of anxiety and the dependent variable of academic performance (−0.247), and a positive and significant correlation exists between the mediator variable of anxiety and the independent variable of academic burnout (0.207). CONCLUSION: Anxiety and academic burnout can reduce students' academic performance. Considering that most students will face stress during their studies for various reasons, coping strategies should be taught to them to prevent their academic burnout and academic failure.